Chapter 7 Manufacturing legislative dominance Gerrymandering and malapportionment - Washida, Hidekuni (Taylor & Francis, 2023)
This chapter explores how the BN had transformed the limited pool of mobilized votes into legislative dominance by tactical gerrymandering and malapportionment. Through the systematic analyses of an originally constructed GIS database of electoral boundaries, this chapter reveals that the optimal gerrymandering strategy under authoritarian party dominance deviates from the conventional wisdom of crack and pack. Specifically, the BN had cracked its supporting base and diffused opposition votes without packing. Moreover, the chapter also demonstrates that wide discretion over mapmaking enabled the leaders to selectively overrepresent their party's supporting base. It also considers the unexpected negative consequences of redistricting.